The Effect of long-term Hydroxychloroquine use on corneal endothelium and thickness - احمد ريم; يوسف سليمان; كاسر الدو (Latakia University Journal -Medical Sciences Series, 2022)
Objective: To study the relationship between long-term Hydroxychloroquine use and the changes in corneal endothelial cells. Methods: In this study, 48 eyes of 24 healthy persons and 48 eyes of rheumatoid patients who used Hydroxychloroquine since a year at least, attending the ophthalmological clinic at Tishreen University Hospital were studied between the years 2021-2022, all participants underwent a complete ophthalmological examination including corneal endothelial cell counts by non contact specular microscopy , where the average of three successive measurements of endothelial cell density (ECD), and hexogram (EX%), coefficient of variation (CV) , central corneal thickness(CCT)were taken. Results: The values of endothelial cell density (ECD) (P ˂ 0.05) decreased and central corneal thickness (P ˂ 0.05) increased statistically significantly, while the value of the covariance (CV) and hexogram(HEX) did not have a statistically significant effect (P> 0.05) from the controls. Conclusion: Patients using long-term HCQ demonstrated lower ECD and higher CCT than the control group.However, the CV and the HEX values were not significantly different from the controls. Keywords: corneal endothelial cells, central corneal thickness, Hydroxychloroquine.